Peran Yayasan Kalimajari dalam Pendampingan Sertifikasi Kakao Lestari di Kecamatan Melaya, Kabupaten Jembrana - IZZAN HADIATMA RAMADHANA; I DEWA PUTU OKA SUARDI; RATNA KOMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
The Role of the Kalimajari Foundation in Assisting Sustainable Cocoa Certification in Melaya Sub-District of Jembrana Regency Assistance is a strategy that will determine the success of a community empowerment program. Assistance as a strategy commonly used by governments and non-profit organizations in an effort to improve the quality of human resources. This research was conducted with the aim to find out about the role of assistance and the level of satisfaction of sustainable cocoa certification assistance in the study area. NGO involvement in community work generally rests on three visions, namely answering humanitarian guidance, carrying out community development efforts towards creating self-help conditions and directing the stages of community development towards the stages of community empowerment. This research was conducted in Melaya Sub-District with a sample of 41 respondents. Samples were obtained from Subak Abian who participated in Sustainable Cocoa Certification. The data analysis method used was a Likert Scale analysis using class intervals 1 to 5. The results showed that the Kalimajari Foundation played a significant role in assisting Sustainable Cocoa Certification in Melaya Sub-District. Assistance activities in the form of representative activities are included in the category of significant roles, assistance activities in the form of facilitation and education activities are classified as quite contributing categories, while assistance in technical activities is classified as less contributing categories. It can be concluded that the Participants of Sustainable Cocoa Certification feel quite satisfied with the assistance provided by the Kalimajari Foundation. Based on the results of the study, the level of satisfaction in the role of representatives classified in the category of satisfaction, the level of satisfaction of the role of facilitation and education is classified in the category of quite satisfied, while the level of satisfaction of the technical role is classified in the category of unsatisfied.